DECISION SUPPORT SYSTEM FOR SOCIAL ASSISTANCE’S BENEFICIARIES USING AHP – PROMETHEE METHOD IN KELURAHAN KARANGANYAR GUNUNG - Aji Supriyanto; Nisa Rahma Ramadhani (Informatika, Universitas Jenderal Soedirman, 2022)
Indonesia as a developing country has problems related to poverty. The government tries to overcome the problem of poverty from year to year by launching various aid programs, one of which is the Family Hope Program (PKH). The distribution of PKH social assistance (bansos) can actually help millions of beneficiaries every year, but there are also obstacles related to the lack of precise targeting of beneficiaries, which often occurs because there is no definite standard in the hierarchy of criteria for beneficiaries. Using the Decision Making System (SPK) with the Analytical Hierarchy Process (AHP) - Preference Ranking Organization Method for Enrichment Evaluation (PROMETHEE) method can provide an alternative to prioritizing aid recipients to assist decisions made by officers and related office holders. The AHP method is used to weight the poverty criteria, while the PROMETHEE method is used to rank the priority of social assistance recipients. Using 45 data on prospective PKH social assistance recipients in Karanganyar Gunung Village who were selected based on 14 poverty criteria, the Central Statistics Agency (BPS) resulted in a priority ranking of social assistance recipients. The ranking is based on the netflow value, the higher the value, the higher the priority level. The ranking using this method gives results in the form of residents with the first priority of receiving social assistance with a net flow value of 0.342 owned by Sumirah followed by Meliyani Kusrini with a net flow value of 0.325.